Effectiveness and safety analysis of Danggui Shaoyao Powder for the treatment of non-alcoholic fatty liver disease: study protocol for a randomized, double-blind, placebo-controlled clinical trial - Qian Huang; Ziming An; Xin Xin; Qinmei Sun; Siting Gao; Sheng Lv; Xiao Xu; Shuohui Yang; Fang Lu; Jie Yuan; Yu Zhao; Yiyang Hu; et al. (BMC, 2023)
Abstract Background The incidence of non-alcoholic fatty liver disease (NAFLD) has been on the rise in recent years, and there are no effective drugs to treat NAFLD; therefore, effective prevention and treatment of NAFLD have become a new challenge. Danggui Shaoyao Powder (DGSY) is a classic prescription commonly used in clinical practice and has been shown to reduce hepatic steatosis in patients with NAFLD. In addition, previous studies have shown that DGSY can alleviate hepatic steatosis and inflammation in NAFLD mice. Although clinical practice and basic studies have shown that DGSY is effective in NAFLD, high levels of clinical evidence are lacking. Therefore, a standardized RCT study protocol is required to evaluate its clinical efficacy and safety. Methods and analysis This study will be a randomized, double-blind, placebo-controlled, and single-center trial. According to the random number table, NAFLD participants will be randomly divided into the DGSY or placebo group for 24 weeks. The follow-up period will be 6 weeks after drug withdrawal. The primary outcome is the relative change in MRI-proton density fat fraction (MRI-PDFF) from baseline to 24 weeks. Absolute changes in serum alanine aminotransferase (ALT), liver stiffness measurement (LSM), body mass index (BMI), blood lipid, blood glucose, and insulin resistance index will be selected as secondary outcomes to comprehensively evaluate the clinical efficacy of DGSY in the treatment of NAFLD. The safety of DGSY will be evaluated by renal function, routine blood and urine tests, and electrocardiogram. Discussion This study will provide evidence-based medical corroboration for the clinical application of DGSY and promote the development and application of this classic prescription. Trial registration http://www.chictr.org.cn . Trial number: ChiCTR2000029144. Registered on 15 Jan 2020.